Analysis of the Impact of Transformational Leadership on Employee Performance in Technology Companies: A Case Study in Jakarta - Jauza, Malenda (Generasi Sains Indonesia, 2024)
This study examines the impact of transformational leadership on employee performance in technology companies in Jakarta. Employing a quantitative research approach, data were collected from 400 employees across three leadership styles: transformational, transactional, and laissez-faire. The results indicate that transformational leadership significantly enhances employee performance compared to the other two leadership styles. Employee engagement was found to mediate the relationship between transformational leadership and performance, highlighting its role in improving outcomes. Statistical analyses, including correlation, regression, and ANOVA, confirmed that transformational leadership leads to higher engagement and performance. The study also identified significant differences in performance based on leadership style, with transformational leadership having the greatest positive effect. This research contributes to the literature by emphasizing the role of leadership in technology companies and the psychological mechanisms through which leadership impacts performance, filling gaps in the existing body of work. The findings suggest that organizations should adopt transformational leadership practices to improve employee outcomes.